2000
DOI: 10.1002/jhet.5570370322
|View full text |Cite
|
Sign up to set email alerts
|

Since 1995 the new chemistry of multicomponent reactions and their libraries, including their heterocyclic chemistry

Abstract: A growing number of products, including many heterocycles, can be prepared by the one‐pot MultiComponent Reactions (MCRs) just by mixing three or more educts, and in many cases practically quantitative yields of pure products can be obtained. The 3CR by α‐aminoalkylations of nucleophiles began in the middle of the last century, and the syntheses of heterocycles by MCRs of three and four components were introduced by Hantzsch in the 1880s. The MCRs of the isocyanides with four and more educts began in 1959, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(72 citation statements)
references
References 66 publications
0
72
0
Order By: Relevance
“…In the midst of prominent efforts to develop new MCRs, 3 Bonfield et al 4 recently reported a resourceful method for the preparation of the isoindoline framework via a six component, tandem double A3-coupling and [2+2+2] cycloaddition reaction. In addition, one-pot, multi-component reactions continue to be of attention in the synthesis of a range of composites containing particularly nitrogen atom 5,6 due to the quick assembly of substituted systems lacking isolation of unstable intermediates. The significance of these one-pot reactions in such syntheses has been well established in the Mannich, Ugi,5 Biginelli, 6 aza-Baylise Hillman 7 reactions, and in Hantzsch dihydropyridine synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of prominent efforts to develop new MCRs, 3 Bonfield et al 4 recently reported a resourceful method for the preparation of the isoindoline framework via a six component, tandem double A3-coupling and [2+2+2] cycloaddition reaction. In addition, one-pot, multi-component reactions continue to be of attention in the synthesis of a range of composites containing particularly nitrogen atom 5,6 due to the quick assembly of substituted systems lacking isolation of unstable intermediates. The significance of these one-pot reactions in such syntheses has been well established in the Mannich, Ugi,5 Biginelli, 6 aza-Baylise Hillman 7 reactions, and in Hantzsch dihydropyridine synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one-pot, multi-component reactions continue to be of attention in the synthesis of a range of composites containing particularly nitrogen atom 5,6 due to the quick assembly of substituted systems lacking isolation of unstable intermediates. The significance of these one-pot reactions in such syntheses has been well established in the Mannich, Ugi,5 Biginelli, 6 aza-Baylise Hillman 7 reactions, and in Hantzsch dihydropyridine synthesis. 8 Furthermore, the Orru group 9 developed a one-pot reaction of up to eight components that involves nine new bond formations and eleven faces of multiplicity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multicomponent reactions (MCRs) have become important tools in modern preparative synthetic chemistry because these reactions increase the efficiency by combining several operational steps without any isolation of intermediates or change of the conditions [1,2] and MCRs have recently emerged as valuable tools in the preparation of structurally diverse chemical libraries of drug-like heterocyclic compounds [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There has been tremendous development in three or four component reaction specially the Bignelli [14], Passerini [15], Ugi [16] and Mannich [17] reactions, which have further led to renaissance of MCRs. MCRs have emerged as valuable tools for the preparation of structurally diverse chemical libraries of drug-like heterocyclic compounds [18][19][20]. Nevertheless, great efforts have been and still are being made to find and develop new MCRs.…”
Section: Introductionmentioning
confidence: 99%